Pengaruh Tingkat Pendidikan Formal Orang Tua Terhadap Hasil Belajar Siswa di Darussalam Kelas VII Kepahiang Bengkulu - Puri Anggraini (GHAITSA : Islamic Education Journal, 2023)
The formulation of the problem in this study is whether there is an effect of the level of formal education of parents on student learning outcomes at MTsS 01 Darussalam class VII Kepahiang Bengkulu. This study aims to determine whether there is a significant effect of the level of formal education of parents on student learning outcomes at MTsS 01 Darussalam class VII Kepahiang Bengkulu. As for. This research method is quantitative research using causal associative quantitative approach. The population used in this study was grade VII students who found 235 students. taking a sample of 10% of the total population, the number of student samples was taken by 23 students by random sampling. Data collection using questionnaires and documentation. Testing of research instruments with validity and reliability tests was carried out on 20 students outside the research subjects. The data analysis technique used is descriptive data technique, prerequisite test, classical assumption test, and hypothesis testing Based on the research, it is explained that there is a significant influence between the level of formal education of parents (X) on the learning outcomes of students (Y) in class VII at MTsS 01 Darussalam Kepahiang Bengkulu. Based on the results of the calculated f test of 0.713 with a significance of 0.000 <0.05. Based on the regression calculation, it can be seen that the coefficient of determination (R square) obtained is 0.708. This means that 70.8% of class VII student learning outcomes at MTsS 01 Darussalam Kepahiang Bengkulu are influenced by the variables of parents' formal education level, while the remaining 29% is 29% of MTsS 01 Darussalam influenced by other variables not studied in the study this.